Thermal Analysis and Battery Modeling of Structural Battery Composites - Dong, Mengyu (My University, 2020)
A thermo-electrochemical finite element analysis (FEA) of a structural battery is presented. A simplified model was developed based on a one-dimensional coordinate in through-thickness direction of the battery. This model simulates the thermal behavior of a structural cell during the (dis)charge cycle. The mathematical model solves the conservation of energy considering heat generations due to only resistive heating. The voltage profile and the heat generation of a structural battery cell with active materials: Carbon fiber/LiFePO4 were studied at different discharge rates. The temperature profile from the pseudo two dimensional (P2D) thermo-electrochemical model had a similar tendency to that from the 3D thermomechanical model. The temperature profile was illustrated at several discharge rates. It was found that the contribution of heat source due to resistive heating was extensive at a high discharge rate. Also the thermal impact of convection condition on the structural battery was analyzed
Keywords: Structural battery; Thermal behavior; Heat generation; Heat exchange; Natural convection